Populism and Democratic Thought in the Canadian Prairies, 1910-1945 - Finkel, Alvin (Labour / Le Travail, 1991)
The article reviews the book, "Populism and Democratic Thought in the Canadian Prairies, 1910-1945," by David Laycock.
Keywords: BOOKS – Reviews; LAYCOCK; David; Nonfiction; POPULISM & Democratic Thought in the Canadian Prairies; 1910-1945 (Book); populism